Histopathological Effects of Tissue Adhesives on Experimental Peripheral Nerve Transection Model in Rats - Altun, Idiris (J Korean Neurosurg Soc, 2015)
OBJECTIVE: Our aim was to evaluate the histopathological effects of tissue adhesives on peripheral nerve regeneration after experimental sciatic nerve transection in rats and to search whether these tissue adhesives may possess a therapeutic potential in peripheral nerve injuries. METHODS: This experimental study was performed using 42 female Wistar-Albino rats distributed in 6 groups subsequent to transection of right sciatic nerves. Group I underwent external circumferential neurolysis; Group II received suture repair; Group III had local polymeric hydrogel based tissue adhesive administration; Group IV received suture repair and polymeric hydrogel based tissue adhesive application together; Group V had gelatin based tissue adhesive application and Group VI had suture repair and gelatin based tissue adhesive together. After a 6-week follow-up period, biopsies were obtained from site of neural injury and groups were compared with respect to histopathological scoring based on inflammatory, degenerative, necrotic and fibrotic changes. RESULTS: There were remarkable differences between control group and study groups with respect to inflammation (p=0.001), degeneration (p=0.002), necrosis (p=0.007), fibrosis (p<0.001) and vascularity (p=0.001). Histopathological scores were similar between study groups and the only noteworthy difference was that Group V displayed a lower score for necrosis and higher score in terms of vascularization. CONCLUSION: Our results imply that tissue adhesives can be useful in repair of peripheral nerve injuries by decreasing the surgical trauma and shortening the duration of intervention. Results with gelatin based tissue adhesive are especially promising since more intense vascularity was observed in tissue after application. However, trials on larger series with longer durations of follow-up are essential for reaching more reliable conclusions.